Mood dimensions show distinct within-subject associations with non-exercise activity in adolescents: an ambulatory assessment study - Koch, Elena; Tost, Heike; Braun, Urs; Gan, Gabriela; Reinhard, Iris; Zipf, Alexander; Meyer-Lindenberg, Andreas (Frontiers in psychology, 2018)
Physical activity is known to preserve both physical and mental health. However, the physical activity levels of a large proportion of adolescents are below the accepted recommendations. This is critical, since physical activity levels in youth have been shown to translate into adulthood, making the promotion of physical activity in adolescence a major health issue. In adult populations, mood has been suggested to be one important psychological factor that drives physical activity in everyday life, i.e., non-exercise activity. However, the association of mood and physical activity in adolescents’ everyday lives has been poorly studied. Ambulatory Assessment is the state-of-the-art approach to investigating how the association between mood and non-exercise activity waxes and wanes within persons in everyday life.